Taxing recurrent services rendered by a foreign company to an associated enterprise in South Africa - Costa, David Patrick Anthony (Rhodes University, Faculty of Commerce, Department of Accounting, 2013)
The objective of the study was to investigate the right of the South African Government to tax the income earned by a foreign company when rendering services in South Africa to a South African associated enterprise on a recurrent basis, together with the right to tax the amounts paid to the employees of the permanent establishment for services rendered in South Africa. At the same time the research investigated whether the services rendered by a foreign company to an associated enterprise in South Africa on a recurrent basis would constitute a permanent establishment, as this is essential before South Africa may tax either the foreign company or the employees of the permanent establishment (where such employees are not resident in South Africa).The research was conducted by means of a critical analysis of documentary data and data from a limited number of interviews with academics and the authors of textbooks and articles. In order to limit the scope of the research, a number of assumptions were made. Conflicting viewpoints underlying certain of these assumptions were discussed. Some of the important conclusions reached are that the provisions of the Vienna Convention on the Law of Treaties should be taken into account when interpreting South African legislation (including Double Tax Agreements), and that the Organisation for Economic Cooperation and Development (OECD) Commentary may be relied upon when interpreting OECD based Double Tax Agreements in South Africa. No conclusion was reached on whether to apply an ambulatory or a static basis of interpreting the OECD Commentary, however. The final conclusion of the research is that the services rendered in South Africa on a recurrent basis would be geographically and commercially coherent and consequently meet the "location test'. It is clear that as the services are rendered regularly and recurrently, they would be regarded as having the necessary permanence and would meet the 'duration test'. The place of business would therefore be regarded as being fixed (having the necessary degree of permanence). As the services would be rendered at the place of business of the South African entity, they would be regarded as being rendered 'through' the place of business and the foreign entity would be regarded as having a permanent establishment in South Africa (as defined in Article 5(1) of the OECD Model Tax Convention}. The South African Government would therefore be entitled to tax the income attributable to the permanent establishment and the income earned by the non resident employees, who rendered services in South Africa for the permanent establishment. Once the entitlement to tax exists, South African legislative rules determine how South Africa proceeds to tax the income.
Keywords: Vienna Convention on the Law of Treaties (1969); Tax administration and procedure -- South Africa; Double taxation -- South Africa; Income tax -- Law and legislation -- South Africa